Right-sided ureteral hemangiosarcoma in a paraplegic dog - Maia, Suellen Rodrigues [UNESP]; Manochio, Mayara; Soares, Lara Vilela; Andrade, Yury Carantino Costa; Alvarenga, Alef Winter Oliveira; Crivellenti, Leandro Zuccolotto (Springer Nature, 2024)
Background: This study aims to describe a rare case of primary ureteral hemangiosarcoma, in which surgical intervention preserved the kidney and ureter after tumor removal. Case presentation: A 13-year-old, neutered male dog, weighing 14 kg, mixed-breed, presented with apathy, anorexia, acute-onset vomiting, and abdominal discomfort during the physical examination. Ultrasonography and pyelography revealed a right-sided dilation of the renal pelvis and ureter due to complete obstruction in the middle third of the ureter. A mass obstructing the lumen of the right ureter was completely resected, and ureteral suturing was performed, preserving the integrity of the involved structures. Histopathology confirmed primary ureteral hemangiosarcoma. Due to the local and non-invasive nature of the mass, chemotherapy was not initiated. The patient’s survival was approximately two years, and normal renal function was preserved throughout this period. Conclusions: Considering this type of tumor in the differential diagnosis of upper urinary tract obstructive disorders. Furthermore, the preservation of the ureter and kidney is a suitable therapeutic option after surgical resection of non-invasive tumors.
Keywords: Hydronephrosis; Pyelography; Ureteral neoplasia; Ureteral obstruction